DERMATOGLIPHIC CHARACTERISTICS AMONG THE MATURATION STAGES OF THE FUTSAL BEGGINER ATHLETES FROM THE POTIGUAR SEMIARID REGION (Fiep Bulletin - online, 2012)
The dermatoglyphics provides access to genetic tendencies that, combined with the contribution of the training environment, can contribute, though not uniquely, to determine the talent and also for its development. The purpose of this study was to determine the characteristics of fingerprints between maturational stages of futsal beginner athletes from the potiguar semiarid region. The methodology used was the digital dermatoglyphics of Cummins and Midi (1942) and the self-assessment protocol by Tanner boards in determining sexual maturation, and as an analytical reference, we used descriptive statistics. The stages studied were the following characteristics in relation to dermatoglyphics: increased presence of (L), followed by (W), lower incidence of (A), and intermediate values of D10 and LQTS; prevalence of digital formulas (10L) (L > W) and (W> L). These data reveal a genetic predisposition to high strength, speed endurance, intermediate levels of coordination and agility, physical qualities considered important for the practice of Futsal.
Keywords: Dermatoglyphics; Futsal; Maturation